2013
DOI: 10.1103/physrevlett.111.203201
|View full text |Cite
|
Sign up to set email alerts
|

New Light Shed on Charge Transfer in FundamentalH++H2Collisions

Abstract: There is no consensus on the magnitude and shape of the charge transfer cross section in low-energy H þ þ H 2 collisions, in spite of the fundamental importance of these collisions. Experiments have thus been carried out in the energy range 15 E 5000 eV. The measurements invalidate previous recommended data for E 200 eV and confirm the existence of a local maximum around 45 eV, which was predicted theoretically. Additionally, vibrationally resolved cross sections allow us to investigate the evolution of the un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…It must be noted that, although Eqs. ( 19) and ( 33) are formally similar, the former one has been derived by using the centrifugal sudden approximation while the Coriolis couplings are not neglected in the semiclassical calculation [see (35)]. This di erence precludes that quantal and semiclassical treatments lead in general to the same results.…”
Section: B Semiclassical Treatmentmentioning
confidence: 81%
See 2 more Smart Citations
“…It must be noted that, although Eqs. ( 19) and ( 33) are formally similar, the former one has been derived by using the centrifugal sudden approximation while the Coriolis couplings are not neglected in the semiclassical calculation [see (35)]. This di erence precludes that quantal and semiclassical treatments lead in general to the same results.…”
Section: B Semiclassical Treatmentmentioning
confidence: 81%
“…This di erence precludes that quantal and semiclassical treatments lead in general to the same results. The validity of this approximation has been discussed in previous works for H + +H 2 collisions [35], where it was found that the cross sections obtained from quantal (IOS) and eikonal semiclassical calculations agree in the range of collision energies 200 eV< E < 400 eV, and therefore both trajectory e ects and centrifugal sudden approximation are not relevant. In general, it is expected that the semiclassical treatment, including rotational couplings, is more accurate at high energies than the IOS one.…”
Section: B Semiclassical Treatmentmentioning
confidence: 94%
See 1 more Smart Citation
“…Previous calculations on ion-diatom collisions ( [35] and references therein) indicates that the approximation is valid for energies above 1 keV/u. In order to describe the electron-target interaction, we have used a threecenter model potential:…”
Section: Methodsmentioning
confidence: 93%
“…Numerous measurements of the cross section of reaction (1) exist, albeit with H 2 in its vibrational ground state and at collision energies well above 10 eV [3]. Our recent work on charge transfer in proton H 2 collisions down to 15 eV [4] demonstrated the decisive role * Electronic address: xavier.urbain@uclouvain.be of the avoided crossing seam connecting the ground and first excited potential energy surfaces of H + 3 . The vibrational population of the H + 2 products was shown to peak at v + = 0 at a collision energy of 45 eV, evolving from a Franck-Condon distribution at keV energies.…”
Section: Introductionmentioning
confidence: 99%